Unmaking waste in production and consumption - Crocker, Robert; Saint, Christopher; Chen, Guanyi; Tong, Yindong (Emerald Publishing Limited, 2018)
This book provides scholars working in the many disciplines that relate to the concept of the Circular Economy with a cross-disciplinary forum, looking at areas such as: Theory, Policy and Contexts; Improving Resource Efficiency and Reducing Waste; Changing Consumption and Behaviour by Design; and Transforming Technologies of Production.